2013
DOI: 10.1016/j.cell.2012.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin 4 Receptors Reciprocally Regulate Sympathetic and Parasympathetic Preganglionic Neurons

Abstract: Summary Melanocortin 4 receptors (MC4Rs) in the central nervous system are key regulators of energy and glucose homeostasis. Notably, obese patients with MC4R mutations are hyperinsulinemic and resistant to obesity-induced hypertension. Although these effects are likely dependent upon the activity of the autonomic nervous system, the cellular effects of MC4Rs on parasympathetic and sympathetic neurons remain undefined. Here, we show that MC4R agonists inhibit parasympathetic preganglionic neurons in the brains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
172
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(185 citation statements)
references
References 31 publications
12
172
1
Order By: Relevance
“…An increased overall SNS activity was evident in rats after the POMC-AAV administration into the NTS, which also fits with our finding (Zhang et al 2010). The inhibition of vagal activity via MC4R has been recently studied ex vivo using electrophysiology and reported to take place in the dorsal motor nucleus of the vagus (DMV) nerve, which receives POMC projections from the NTS (Sohn et al 2013). Our results show that the inhibition of vagal activity is evident in vivo and is sustained when a-MSH is overexpressed in the NTS neurons.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…An increased overall SNS activity was evident in rats after the POMC-AAV administration into the NTS, which also fits with our finding (Zhang et al 2010). The inhibition of vagal activity via MC4R has been recently studied ex vivo using electrophysiology and reported to take place in the dorsal motor nucleus of the vagus (DMV) nerve, which receives POMC projections from the NTS (Sohn et al 2013). Our results show that the inhibition of vagal activity is evident in vivo and is sustained when a-MSH is overexpressed in the NTS neurons.…”
Section: Discussionsupporting
confidence: 78%
“…However, a-MSH has also been demonstrated to regulate insulin levels and glucose homeostasis independent of the changes in body weight via regulation of the autonomic nervous system (Obici et al 2001, Rossi et al 2011, Sohn et al 2013. Recent research using cell-specific genetic manipulation of Mc4r has demonstrated the key role of MC4R in the cholinergic neurons in inhibition of parasympathetic neurons and activation of sympathetic neurons leading to changes in energy, glucose, and cardiovascular homeostasis (Rossi et al 2011, Sohn et al 2013. Although the analysis of HR control by the autonomic nervous system showed an increased sympathetic tone and a decreased parasympathetic tone, it was not reflected to the longterm changes in insulin and glucose levels in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the question of how the central insulin action actually controls the vagus nerve activity via hypothalamic neurons and suppresses HGP remains unanswered. HGP is also suppressed by icv administration of α-MSH [35], and according to a patch clamp study, the agonist of melanocortin receptor, which is the receptor of α-MSH, causes hyperpolarization of DMV neurons [36]. In addition, it has been revealed that diazoxide, which activates K ATP channel and induce hyperpolarization of neurons, suppresses HGP when administered to DMV [37].…”
Section: Central Insulin Action and The Vagus Nervementioning
confidence: 99%
“…MC4R has been associated with key components of nutrient absorption, lipid metabolism, energy expenditure, thermogenesis, adiposity, insulin secretion, food intake, and appetite (Adan et al 2006). Moreover, the MC pathway interacts with other key hormones or pathways such as leptin, 5-HT (Zhou et al 2007), NPY, AGRP, POMC (Biebermann et al 2012), and ANS (Rossi et al 2011;Sohn et al 2013) in the hypothalamus and brainstem (Loos 2011), GLP-1 pathway (Gautron et al 2010), CCK, and vagal afferent fibers (Guan et al 2012).…”
Section: Introductionmentioning
confidence: 99%